An electronic registry to improve adherence to active surveillance monitoring among men with prostate cancer at a safety-net hospital: protocol for a pilot study - Cedars, Benjamin; Lisker, Sarah; Borno, Hala T.; Kamal, Puneet; Breyer, Benjamin; Sarkar, Urmimala (Pilot and feasibility studies, 2019)
Background The evidence-based practice of active surveillance to monitor men with favorable-risk prostate cancer in lieu of initial definitive treatment is becoming more common. However, there are barriers to effective implementation, particularly in low-resource settings. Our goal is to assess the efficacy and feasibility of a health information technology registry for men on active surveillance at a safety-net hospital to ensure patients receive guideline-recommended care. Methods We developed an electronic registry for urology clinic staff to monitor men on active surveillance. The health information technology tool was developed using the Systems Engineering Initiative for Patient Safety model and iteratively tailored to the needs of the clinic by engaging providers in a co-design process. We will enroll all men at Zuckerberg San Francisco General Hospital and Trauma Center who choose active surveillance as a treatment strategy. The primary outcomes to be assessed during this non-randomized, pragmatic evaluation are number of days delayed beyond recommended date of follow-up testing, the proportion of men who are lost to follow-up, the cancer stage at active treatment, and the feasibility and acceptability of the clinic-wide intervention with clinic staff. Secondary outcomes include appointment adherence within 30 days of the scheduled date. Discussion Use of a customized electronic approach for monitoring men on active surveillance could improve patient outcomes. It may help reduce the number of men lost to follow-up and improve adherence to timely follow-up testing. Evaluating the adoption and efficacy of a customized registry in a safety-net setting may also demonstrate feasibility for implementation in diverse clinical contexts. Trial registration ClinicalTrials.gov identifier NCT03553732 , An Electronic Registry to Improve Adherence to Active Surveillance Monitoring at a Safety-net Hospital. Registered 11 June 2018.